Simulação numérica e avaliação sistemática do atrito transiente em transientes gerados por falhas no conjunto moto-bomba em adutoras de recalque - Ferreira, Fábio Eduardo Franco Rodrigues (2016)
The analysis of hydraulic transients is a useful tool for risk and system efficiency management of pump-pipeline systems. Problems associated with water hammer and system economy can be attenuated by more accurate predictions. Inverse transient analysis for leaks or blockages detection can also benefit from more accurate models. The elastical model has several lacks concerning the energy dissipation modelling. Unsteady friction models has been fundamental to accurately describe the energy dissipation in hydraulic transient. However, the absence of well-defined evaluation criteria and the presence of noise in the measurements hinders a general agreement concerning the unsteady friction models. This research focuses on developing a hydraulic simulator that consider the unsteady friction. An experimental data filtering method and a performance evaluation method of hydraulic transient model were also developed